2017
DOI: 10.1186/s13014-017-0841-9
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy for older patients with brain tumors

Abstract: The incidence of brain tumors in the elderly population has increased over the last few decades. Current treatment includes surgery, radiotherapy and chemotherapy, but the optimal management of older patients with brain tumors remains a matter of debate, since aggressive radiation treatments in this population may be associated with high risks of neurological toxicity and deterioration of quality of life. For such patients, a careful clinical status assessment is mandatory both for clinical decision making and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 152 publications
1
29
0
Order By: Relevance
“…In addition to the less favorable tumor biology and comorbidities associated with advanced age, it is possible that the shorter OS in older patients can be partly attributed to their lesser likelihood of receiving trimodality therapy, which has been shown in our study to improve OS regardless of age. The concern about adjuvant RT in elderly glioblastoma patients is neurotoxicity, which would outweigh any survival benefit conferred by RT [38][39][40]. The link between comorbidity and receipt of treatment remains unclear, even in glioblastoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the less favorable tumor biology and comorbidities associated with advanced age, it is possible that the shorter OS in older patients can be partly attributed to their lesser likelihood of receiving trimodality therapy, which has been shown in our study to improve OS regardless of age. The concern about adjuvant RT in elderly glioblastoma patients is neurotoxicity, which would outweigh any survival benefit conferred by RT [38][39][40]. The link between comorbidity and receipt of treatment remains unclear, even in glioblastoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…This prospective study was conducted from January 2015 to December 2017 in a hospital with more than 1,500 beds; data collection was performed prior to the initiation of CRT, 2-3 weeks after the initiation of CRT, and 4-6 weeks after the initiation of CRT. In our study, CRT was performed three times in accordance with the previous study (Davis, 2016;Minniti et al, 2017), which described the most frequently observed symptoms in patients with CRT. Convenience sampling was conducted in a hospital or outpatient clinic.…”
Section: Study Design and Samplingmentioning
confidence: 96%
“…RTOG criteria for CI determine the quality of conformity. 2,24 Due to the emphasis of this study to recommend the DGI guidelines for intracranial SRS/SRT treatments, only plans that were ideal per RTOG 0915 1 and 0813 2 (1 CI < 1.2) were considered.…”
Section: CImentioning
confidence: 99%
“…It has been demonstrated to increase patient survival rates and improve quality of life. 1,2 The conventional treatment technique for both identifiable brain metastasis and prophylaxis for microscopic disease is stereotactic radiosurgery (SRS)/stereotactic radiation therapy (SRT) with or without whole brain radiation therapy. 3 SRS provides accurate delivery of a high dose of radiation to a target in a single fraction while sparing the surrounding normal tissue.…”
Section: Introductionmentioning
confidence: 99%